LIQUEFACTION POTENTIAL ANALYSIS BASED ON THE GLOBAL GEOSPATIAL MODEL (GGM) METHOD IN TARUTUNG DISTRICT - Nova Aulia Rahma Nasution; Ratni Sirait; Russell Ong; Sugeng (RADJA PUBLIKA, 2025)
This study focuses on knowing the Vs30 value in Tarutung District, knowing the Peak Ground Velocity (PGV) value in Tarutung District, knowing the potential for liquefaction in Tarutung District using the Global Geospatial Model (GGM) method. The results of this study are that the Vs30 value in Tarutung District has a distribution in the range of 255 M / S which is in the North to the Northeast and covers almost half of the Tarutung District area with a classification of medium soil type, very dense soil or soft rock, up to 897.8 M / S which is spread in the lower southwest direction of Tarutung District to several points to the southeast of Tarutung District with a classification of very dense soil type or soft rock and rock. The PGV value in Tarutung District based on the worst earthquake scenario in the Toru segment of the Sumatran fault varies in the range of 7.94 cm/s to 15.20 cm/s. The potential for liquefaction in Tarutung District based on the Global Geospatial Model has various values. The lowest percentage value of liquefaction probability is 0.024, which is in the north, southeast, and northwest of Tarutung District, and the highest percentage value of probability is 0.961, which is in the northeast and southwest of Tarutung District.